2021
DOI: 10.7150/ijbs.62001
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and clinical progress for HDAC as a putative target for epigenetic remodeling and functionality of immune cells

Abstract: Genetic changes are difficult to reverse; thus, epigenetic aberrations, including changes in DNA methylation, histone modifications, and noncoding RNAs, with potential reversibility, have attracted attention as pharmaceutical targets. The current paradigm is that histone deacetylases (HDACs) regulate gene expression via deacetylation of histone and nonhistone proteins or by forming corepressor complexes with transcription factors. The emergence of epigenetic tools related to HDACs can be used as diagnostic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 206 publications
(216 reference statements)
0
8
0
Order By: Relevance
“…We also found that XQLD could downregulate the expression of HDAC1, HDAC3, and HDAC4. HDAC has been recognized it is closely related to immune regulation and can regulate the innate and adaptative immune response [20,21]. Recently, HDAC has been found it could also regulate the proliferation of type 2 innate lymphoid cells in airway inflammation [22] and modulate effector T cell phenotypes in severe COVID-19 patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that XQLD could downregulate the expression of HDAC1, HDAC3, and HDAC4. HDAC has been recognized it is closely related to immune regulation and can regulate the innate and adaptative immune response [20,21]. Recently, HDAC has been found it could also regulate the proliferation of type 2 innate lymphoid cells in airway inflammation [22] and modulate effector T cell phenotypes in severe COVID-19 patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HDAC regulators play an indispensable role in regulating the TME [17,38]. Most previous studies have explored the function of a single HDAC or a class of HDACs, but different HDACs play highly heterogeneous roles in regulating the TME and antitumor effects [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, deacetylation of histones has the opposite effect [14]. HDACs reversibly regulate the acetylation status of histones and nonhistone proteins during TME development [15][16][17]. Moreover, HDAC6 is involved in the upregulation of several key factors in the immune system, such as PD-1 and PD-L1 receptors, which are the main cancer immunotherapy targets [18].…”
Section: Ivyspringmentioning
confidence: 99%
“…Meanwhile, the level of HDAC11 correlates with the function of neutrophils. Neutrophils lacking HDAC11 are better able to cope with LPS-induced sepsis, granulocyte expansion, and increased extramedullary hematopoiesis, showing increased migration of inflammatory cytokines and phagocytosis [ 101 , 102 ]. The use of different concentrations of HDAC inhibitors (HDACis), belinostat, and panobinostat, to promote histone acetylation revealed a shift in the type of neutrophil death from NETosis to apoptosis.…”
Section: Histone Modifications In Sepsis Immunity and Progressionmentioning
confidence: 99%